Impact of Penicillin V-Induced Gut Dysbiosis During Pregnancy on Early Life Immune Outcomes Through the Gut-Spleen Axis - Kaur, Manmeet (Université d'Ottawa / University of Ottawa, 2026)
Pregnancy and early postnatal life constitute critical developmental windows during which maternal disturbances can exert lasting effects on both maternal and offspring health according to the Developmental Origins of Health and Disease (DOHaD) hypothesis. Antibiotic-induced gut microbiota dysbiosis by intrapartum antibiotic prophylaxis (IAP) may lead to potential long-term consequences for immune education and metabolic programming in the offspring. We investigated the impact of maternal low dose penicillin V (LDP) exposure in balb/c mice to characterize its transient effects on maternal mucosal and splenic immunity and its long-term consequences on gut-spleen immune crosstalk and microRNA-mediated regulation in the offspring. We further evaluated kefir supplementation as a nutritional intervention to mitigate these effects on maternal and offspring gut–immune crosstalk. Based on our findings, maternal LDP exposure did not produce lasting changes in mucosal and splenic immune outcomes in the offspring, whereas kefir supplementation improved intestinal IgA/IgG levels and splenic FOXP3/RORγt–mediated immune homeostasis. These findings were consistent with microbiota-associated modulation of gut homeostasis in female offspring, underscoring the contribution of commensal microbial communities in regulating IgA/IgG-mediated mucosal responses and gut–spleen immune crosstalk. These immune outcomes were accompanied by altered expression of intestinal microRNAs in offspring, including miR-155, miR-146a, and members of the let-7 family, indicating a genomic imprint of early-life microbial exposure on host immune regulation. These changes exhibited clear sex-specific patterns, further underscoring the influence of developmental and hormonal context in shaping immune programming. Additionally, maternal antibiotic exposure combined with kefir supplementation was associated with differential regulation of microRNAs implicated in pathways relevant to neuroimmune regulation, including miR-155 suggesting broader systemic effects extending beyond immune modulation alone. Overall, this study provides mechanistic evidence supporting the existence of a functional gut–spleen axis, demonstrating that early-life microbial environments can induce persistent, sex-dependent immunological outcomes until puberty, highlighting the long-term impact of early life gut microbiome environment.
Keywords: Gut Microbiome; Gut-Spleen Axis; Developmental Origins of Health and Disease (DOHaD); Intrapartum Antibiotic Prophylaxis (IAP); Kefir; Probiotics; Mucosal Immunity